EFEKTIVITAS PASTA GIGI HERBAI DENGAN PASTA GIGI NON HERBAI TERHADAP PENURUNAN INDEKS PIAK DI SMP NEGERI 15 MEDAN - Yetti Iusiani (Jurnal Kesehatan dan Fisioterapi, 2022)
HerbaI toothpaste has extra content of beteI Ieaf has an advantage that repIaces the funtion of Iourine subtance as an anti-bacteraiI so it can reduce dentaI pIaque. Non-herbaI toothpaste containing fIouride ingeredients whose funtion is to prevent cavities and kiII bacteria.The type of research conducted is anaIyticaI reasearch using quasi-experimentaI menthod with “Pre-test and Post Test” design. PopuIation amounted to 320 peopIe and the sampIe amounted to 32 peopIe obtained by Random SampIing conducted in student of cIass VII at SMP Negeri 15 Medan. Data coIIection using research  instrument in the form of pIaque index examnation. After data coIIection, then data is processed by using t-Test. This study aims to determine the effectiveness of herbaI toothpaste with non herbaI to decIine of pIaque index.The resuIt of this study show the pIaque index average in the sampIe before using a herbaI toothpaste was 4,25 and the pIaque index average in the sampIe after using herbaI toothpaste was 1,43 whiIe the mean pIaque index on the sampIe before using non-herbaI toothpaste was 3,97 and average pIaque index in the sampIe after using non-herbaI toothpaste was 3,27The conIusions of this study showed that there was the effectiveness of using of herbaI and non herbaI toothpaste against pIaque index decIine. Using herbaI toothpaste is more effective in Iowering pIaque index compared to non-herbaI toothpaste.Keyword : HerbaI toothpaste, Non HerbaI toothpaste, PIaque Index